DAYA TERIMA PEMBUATAN MI BASAH DENGAN PENAMBAHAN TEPUNG DAUN KELOR - Salim, Nur; zakaria, zakaria; Wulandari, Desi (Jurusan Gizi Poltekkes Kemenkes Makassar, 2020)
Background: Mie is one of the staple food that consumed by many people, the problem is minerals and vitamins in the mie is very limited. Therefore it need an effort to add more vitamins and minerals in the mie, one of the ways is adding Moringa leaf powder to the mie. Moringa leaves is a plant that contains nutrients that nearly meet the human nutritional needs and useful as a nutritional improvement.Objectives: This research aims to know acceptability manufacture of wet noodle with adding Moringa leaf powder.Methods: This research is eksperimen research with the study design post test control design.Results: This research’s result is show that acceptability of wet noodle with adding Moringa leaf powder that most preferred is formula with concentration 2% and color aspect as much as 52%, taste aspect as much as 56%, aroma aspect as much as 36%, and texture aspect as much as 52%. Statistical results of anova test showed that there is the effect of adding Moringa leaf powder so followed by Tukey test stating that the panelists gave significantly different assessments (p < 0,05) of the wet noodles with the addition of moringa leaf powder. Comparison of the best material that is preferred by the panelists wet noodles with the addition of Moringa leaf powder is formula concentration of 2% with every additional 20 grams of Moringa leaf powder. Wet noodle received power with the addition of Moringa leaf powder is the most preferred concentration of 2%.Suggestion: It is suggested for further research conduct laboratory testing of nutrient content in the wet noodles with the addition of moringa leaf powder and formula concentration of 2%.Keywords : Acceptability,Wet Noodle, Moringa leaves